Current treatments used in clinical practice for major depressive disorder and treatment resistant depression in England: A retrospective database study. (July 2021) - Denee, Tom; Kerr, Cicely; Ming, Timothy; Wood, Robert; Tritton, Theo; Middleton-Dalby, Chloe; Massey, Olivia; Desai, Mitesh
Abstract: Background: Major depressive disorder (MDD) is a chronic recurrent or episodic psychiatric illness that can be successfully treated with oral antidepressants, yet one-in-three patients do not respond to currently-available treatments. According to the FDA and EMA, patients are considered to have treatment-resistant depression (TRD) when their MDD fails to respond adequately to ≥2 successive antidepressants in a single episode. Aims: To describe current clinical management of patients with MDD and TRD in England, including treatment strategies and referral to secondary mental healthcare. Method: A retrospective cohort study of adult patients identified in primary care with diagnosed MDD, including a TRD subgroup (≥2 treatment failures as determined by treatment dynamics) was conducted using the Clinical Practice Research Datalink GOLD primary care database linked to Hospital Episode Statistics and Mental Health Services Data Set data (Protocol 19_019R). Results: 41, 375 patients with MDD (mean age 44yrs, 62% female, median follow-up 29mths); and 1, 051 (3%) patients with TRD were identified. Mean time-to-TRD was 18 months. Most patients (>99%) received first-line antidepressant monotherapy. Following TRD criteria being met, antidepressant monotherapy use remained most frequent from TRD first-line (70%) to fifth-line (48%). Dual/triple antidepressant use remained constant (range:24%–26%), while augmented antidepressant use increased from TRD first-line (7%) to third-line (17%). Minimal non-pharmacological therapies were observed. Conclusions: Despite current clinical guidelines recommending a stepwise approach, many patients frequently cycle through numerous antidepressants with similar mechanisms of action and efficacy. These findings indicate a high unmet need for new treatments that improve outcomes in these patient populations. Highlights: We describe current clinical management of patients with MDD and TRD in England (81 characters). Patients frequently cycle through antidepressants with similar mechanisms of action (85 characters). Clinical depression guidelines are not always followed in UK clinical practice (80 characters). There is a need for more effective treatments to reduce patients cycling through similar therapies (84 characters).